Cambridge o level biology - Mackean, D. G.; Hayward, Dave (Hodder Education London, 2021)
This title has been endorsed by Cambridge Assessment International Education. Written by renowned expert authors, our updated resources enable the learner to effectively navigate through the content of the revised Cambridge O Level Biology (5090) syllabus for examination from 2023. - Develop strong practical skills: practical skills features provide guidance on key experiments, interpreting experimental data, and evaluating results; supported by practice questions for preparation for practical exams or alternatives. - Build mathematical skills: worked examples demonstrate the key mathematical skills in scientific contexts; supported by follow-up questions to put these skills into practice. - Consolidate skills and check understanding: self-assessment questions, exam-style questions and checklists are embedded throughout the book, alongside key definitions of technical terms and a Glossary. - Navigate the syllabus confidently: content flagged clearly with introductions to each topic outlining the learning objectives and context. - Deepen and enhance scientific knowledge: going further boxes throughout encourage students to take learning to the next level.